2020
DOI: 10.1016/j.ejso.2020.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative breast MRI in management of patients with needle biopsy-proven ductal carcinoma in situ (DCIS)

Abstract: Background: In 20e25% of patients with biopsy-proven DCIS underestimation occurs. Sentinel lymph node biopsy (SLNB) is offered to patients with biopsy-proven ductal carcinoma in situ (DCIS) and a high risk of occult invasive cancer. However, assessment of high risk is controversial. We aimed to improve selection of patients for SLNB with preoperative breast magnetic resonance imaging (MRI). Methods: In this prospective observational study, MRI was offered to all subsequent patients with a biopsy-proven DCIS ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Preoperative magnetic resonance imaging (MRI) has not been found reliable to predict invasive disease in prospective evaluation. 25 Vacuum-assisted biopsies (VAB) lower the rate of postoperative upstaging to invasive cancer to 17-18% in retrospective studies, 26,27 but, in larger cohorts, the rate of underestimation was as high as 25%. 28 In the prospective CINNAMOME trial (patients with VAB diagnosis of DCIS, planned for mastectomy, average DCIS extent: 69 mm, Grade 3: 51%), the underestimation rate as high as 39%, and it was suggested that upfront SLND should be performed when mastectomy is planned.…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative magnetic resonance imaging (MRI) has not been found reliable to predict invasive disease in prospective evaluation. 25 Vacuum-assisted biopsies (VAB) lower the rate of postoperative upstaging to invasive cancer to 17-18% in retrospective studies, 26,27 but, in larger cohorts, the rate of underestimation was as high as 25%. 28 In the prospective CINNAMOME trial (patients with VAB diagnosis of DCIS, planned for mastectomy, average DCIS extent: 69 mm, Grade 3: 51%), the underestimation rate as high as 39%, and it was suggested that upfront SLND should be performed when mastectomy is planned.…”
Section: Discussionmentioning
confidence: 99%
“…The feasibility of traditional clinicopathologic risk factors for the postoperative pathological upstaging of DCIS has been reported, 5,11–13 but the prediction performance was dissatisfactory 14–17 . Against this background, MRI could serve as an effective examination tool for the diagnosis and staging of breast cancer, 18,19 but for radiologists, it is quite challenging to assess whether DCIS has invasive components and to define the nuclear grade based on images 20–22 …”
mentioning
confidence: 99%
“…[14][15][16][17] Against this background, MRI could serve as an effective examination tool for the diagnosis and staging of breast cancer, 18,19 but for radiologists, it is quite challenging to assess whether DCIS has invasive components and to define the nuclear grade based on images. [20][21][22] With the emergence of radiomics, medical images can be quantitatively converted into mineable data to improve diagnosis and prognosis assessment and to guide clinical treatment decision-making. 23,24 The feasibility has been demonstrated by predicting the upstaging of DCIS based on single-sequence MRI radiomics.…”
mentioning
confidence: 99%